PERBANDINGAN KADAR ASPAL HASIL EKTRAKSI PADA CAMPURAN ASPAL AC-BC - Fitridawati Soehardi (Jurnal Teknik Sipil Unaya, 2017)
The purpose of this study is the comparison of asphalt content of extracted results on the mixture (AC-BC) in accordance with the 2010 revision of the reflex 3. The method used in this study by extraction using a centrifuge extractor on three specimens of test specimens derived from AMP , The asphalt finisher blend of asphalt from the back of the Asphalt Finisher machine and the compaction result taken using Coredrill using a pertaline solvent. This research includes testing of asphalt content before and after Ektraksi. Based on the results of research The percentage of asphalt extraction results from the 6 test objects from each sample obtained the average value of AMP, finisher, and coredrill is 5.60%, 5.58%, 5.49%. Based on the results of the study Comparison of extraction rate by using a solvent of pertalite, from extraction test of Asphalt Mixing Plant asphalt content, Asphalt Finisher, Coredrill asphalt value decreasing from JMF. So that can be made formulation KA Job Mix Formula (JMF) = KA Asphalt Mixing Plant (AMP)> KA when overlaying> KA core. Average: 5.60% ≧ 5.60%> 5.58%> 5.49%. The extraction results are far from the minimum tolerance threshold of the mixture according to Binamarga 2010 2010 revision 3 (three) specifications. Therefore, this study may also support the statement on the Binamarga 2010 revision 3 (three) specification which states core test should not be used for extraction testing.